Thermogravimetric studies of a nasal preparation with an interleukin-1β (IL-1Ra) antagonist - B. S. Burlaka (Zaporozhye State Medical University, 2021)
Interleukin-1 receptor antagonist (IL-1Ra) is an active pharmaceutical ingredient obtained by the method of gene transformation of Escherichia coli, provides a neuroprotective effect, namely - inhibition of oxidative modification of proteins, normalization of functional activity of mitochondrial energy, mitochondrial energy. Early complex physical-chemical, microbiological, and biopharmaceutical studies have developed a new intranasal formulation, the formulation of which contains: IL-1Ra, sodium carboxymethyl cellulose, D-panthenol, benzalkonium chloride, trilon B, Tween-80, phosphate buffer solution. Given the peculiarities of the technological process, when creating a new gel dosage form, it is necessary to justify the temperature of the carrier base, the introduction of the active substance into the base, as well as to predict the possible chemical interaction of individual components in the dosage form. Therefore, the application of thermogravimetric analysis in pharmaceutical technology is relevant. The aim of the work is to conduct thermogravimetric studies of a new nasal form with an antagonist of interleukin-1β (IL-1Ra). Materials and methods. The objects of thermogravimetric studies were: semi-finished product-solution of the receptor antagonist of interleukin-1 (IL-1Ra). Excipients were: sodium carboxymethylcellulose, tween-80, D-panthenol, trilon B, benzalkonium chloride. To ensure the appropriate pH value used phosphate buffer solution (pH 6.0), according to the recipe to State Pharmacopoeia 2 ed. In addition to the individual components of the finished nasal gel, also prepared nasal gel without IL-1Ra, as well as gel with IL-1Ra. The thermographic analysis was performed on a derivatograph - Shimadzu DTG-60 (Japan) with a platinum-platinum-rhodium thermocouple when heating the samples in aluminum crucibles (from 15 °C to 250 °C). Al2O3 was used as a reference substance. The heating rate was 10 °C per minute. The weight of the test samples ranged from 19.22 mg to 52.91 mg. The derivatograph graphically recorded the obtained data in the form of curves T, DTA, TGA. The T curve on the derivatogram shows the change in temperature, and the TGA curve shows the change in mass of the sample during the study period. The DTA curve reflects the differentiation of thermal effects, contains information about endothermic and exothermic maxima, can be used for qualitative evaluation of the derivatogram. Results. The study consisted of two stages. At the first stage, we studied the derivatograms of experimental samples - individual ingredients of the finished nasal gel - active and excipients, namely: IL-1Ra, sodium carboxymethylcellulose, tween-80, D-panthenol, trilon B, benzalkonium chloride, phosphate buffer solution 6.0. In the second stage, samples of nasal gels were prepared: nasal gel with the required amount of excipients, in addition to the active substance - IL-1Ra, as well as a nasal gel containing IL-1Ra and the required amount of excipients. As a result, we obtained some parameters of thermogravimetric analysis in the form of a graphical image - derivatograms, which were then analyzed. Conclusions. Thermogravimetric studies of individual components of nasal gel with IL-1Ra, as well as nasal gels with active substance and without active substance, were found that the manufacturing process of gel with IL-1Ra should be carried out taking into account thermolabile compounds. First, you need to prepare the base without preservative and IL-1Ra. Then at a temperature not exceeding 40 °C dissolve the preservative, and then when cooled to 20 °C add IL-1Ra. It was found that the developed dosage form of the gel with IL-1Ra is a mixture of active and excipients, the ingredients of which do not interact with each other and can be combined in one dosage form.